U.S. North Pacific Surveying Expedition, Lieutenant John Rodgers, Commanding. Aleutian Archipelago, sheet no. 1 by the U.S. Schr. Fenimore Cooper - United States North Pacific Exploring Expedition (1853-1856) (Washington, D.C. : United States North Pacific Exploring Expedition, 1855)
July & August 1855 Grayscale; 1:700,000